Randomized controlled multicentre study comparing biological mesh closure of the pelvic floor with primary perineal wound closure after extralevator abdominoperineal resection for rectal cancer (BIOPEX-study) - Musters, Gijsbert D (BioMed Central, 2014)
BACKGROUND: Primary perineal wound closure after conventional abdominoperineal resection (cAPR) for rectal cancer has been the standard of care for many years. Since the introduction of neo-adjuvant radiotherapy and the extralevator APR (eAPR), oncological outcome has been improved, but at the cost of increased rates of perineal wound healing problems and perineal hernia. This has progressively increased the use of biological meshes, although not supported by sufficient evidence. The aim of this study is to determine the effectiveness of pelvic floor reconstruction using a biological mesh after standardized eAPR with neo-adjuvant (chemo)radiotherapy compared to primary perineal wound closure. METHODS/DESIGN: In this multicentre randomized controlled trial, patients with a clinical diagnosis of primary rectal cancer who are scheduled for eAPR after neo-adjuvant (chemo)radiotherapy will be considered eligible. Exclusion criteria are prior radiotherapy, sacral resection above S4/S5, allergy to pig products or polysorbate, collagen disorders, and severe systemic diseases affecting wound healing, except for diabetes. After informed consent, 104 patients will be randomized between standard care using primary wound closure of the perineum and the experimental arm consisting of suturing a biological mesh derived from porcine dermis in the pelvic floor defect, followed by perineal closure similar to the control arm. Patients will be followed for one year after the intervention and outcome assessors and patients will be blinded for the study treatment. The primary endpoint is the percentage of uncomplicated perineal wound healing, defined as a Southampton wound score of less than II on day 30. Secondary endpoints are hospital stay, incidence of perineal hernia, quality of life, and costs. DISCUSSION: The BIOPEX-study is the first randomized controlled multicentre study to determine the additive value of using a biological mesh for perineal wound closure after eAPR with neo-adjuvant radiotherapy compared to primary perineal wound closure with regard to perineal wound healing and the occurrence of perineal hernia. TRAIL REGISTRATION NUMBER: NCT01927497 (Clinicaltrial.gov).